2011
DOI: 10.1111/j.1758-2229.2011.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Quorum-sensing quenching by rhizobacterial volatiles

Abstract: We show that volatile organic compounds (VOCs) produced by rhizospheric strains Pseudomonas fluorescens B-4117 and Serratia plymuthica IC1270 may act as inhibitors of the cell-cell communication quorum-sensing (QS) network mediated by N-acyl homoserine lactone (AHL) signal molecules produced by various bacteria, including strains of Agrobacterium, Chromobacterium, Pectobacterium and Pseudomonas. This quorum-quenching effect was observed when AHL-producing bacteria were treated with VOCs emitted by strains B-41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 25 publications
3
69
0
2
Order By: Relevance
“…For example, volatiles produced by S. plymuthica can inhibit cell-cell communication mediated by acyl homoserine lactone molecules in Agrobacterium, Pectobacterium and Pseudomonas. Volatiles emitted by S. plymuthica decreased the amount of acyl homoserine lactone produced by these bacteria, leading to significant suppression of transcription of acyl homoserine lactone synthase genes (Chernin et al, 2011).…”
Section: Volatile Affairs In Microbial Interactions R Schmidt Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…For example, volatiles produced by S. plymuthica can inhibit cell-cell communication mediated by acyl homoserine lactone molecules in Agrobacterium, Pectobacterium and Pseudomonas. Volatiles emitted by S. plymuthica decreased the amount of acyl homoserine lactone produced by these bacteria, leading to significant suppression of transcription of acyl homoserine lactone synthase genes (Chernin et al, 2011).…”
Section: Volatile Affairs In Microbial Interactions R Schmidt Et Almentioning
confidence: 99%
“…The fact that the production of antibiotics in these bacteria is regulated by quorum sensing (QS) suggests that volatiles may interfere with bacterial cell-cell communication. Indeed, several studies revealed that volatiles can affect QS systems in bacteria, negatively or positively (Schulz et al, 2010;Chernin et al, 2011;Ahmad et al, 2014). For example, volatiles produced by S. plymuthica can inhibit cell-cell communication mediated by acyl homoserine lactone molecules in Agrobacterium, Pectobacterium and Pseudomonas.…”
Section: Volatile Affairs In Microbial Interactions R Schmidt Et Almentioning
confidence: 99%
“…Highly significant volatile-mediated effects of bacteria have been reported for various target organisms, including bacteria themselves (1)(2)(3)(4)(5), plants (5)(6)(7)(8)(9), and fungi (10)(11)(12). The research carried out to understand the nature of this volatile-mediated interaction of bacteria with plants and with other bacteria has focused so far on model organisms (e.g., Arabidopsis thaliana and Escherichia coli) and has enabled identification of some of the active compounds involved in the respective interactions, such as indole, 2,3-butanediol, dimethyl disulfide, hydrogen sulfide, and ammonia.…”
mentioning
confidence: 99%
“…Volatiles exposed colonies showed reduced growth and white coloration indicating the lack of prodigiosin production. It is plausible that this observation is related to the inhibition of quorum sensing as previously reported by Moroshi and Chernin (Morohoshi et al, 2007;Chernin et al, 2011).…”
Section: Discussionsupporting
confidence: 77%
“…These physiochemical properties make volatiles ideal metabolites for communication and antagonistic interactions between soil microorganisms living at a certain distance from each other. Indeed, recent studies indicate that soil microorganisms can employ volatile compounds as info-chemicals, growth stimulants, growth inhibitors and inhibitors of quorum-sensing (Kai et al, 2009;Chernin et al, 2011;Effmert et al, 2012;Kim et al, 2013). Furthermore, rhizosphere bacteria emit volatiles that can promote plant growth and elicit induced systemic resistance (ISR) and induced systemic tolerance (IST) in plants (Ryu et al, 2003;Ryu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%